Efektivitas Structure Learning Approach (SLA) untuk Meningkatkan Kompetensi Guru dalam Memandirikan Siswa SD yang terReject di Wilayah KKG Kapanewon Sleman - Aprilia Lidyasari; Albi Anggito; Anwar Senen; Firmansyah Firmansyah; Sekar Purbarini Kawuryan; Mujinem Mujinem (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2022)
The Covid-19 pandemic has an impact on all aspects of life, including the social life of elementary school children. This study aims to determine the effectiveness of the structure learning (SLA) approach to improve teacher competence in independent elementary school students who are rejected in the KKG Kapanewon Sleman area. This research uses quantitative research with pre-experimental method with one group pretest-posttest design which is by comparing the condition before being given treatment and the condition after being given treatment. This study involved 25 teachers who were members of the teacher working group (KKG) in Kapanewon Sleman, Yogyakarta Special Region which was held in July-September 2022. This improvement used the lecture, question and answer, discussion, simulation and project methods. The data collection technique used is observation and the structure learning approach (SLA) scale. While the technical analysis of the data using the Wilcoxon Test. The Structure Learning Approach (SLA) has 5 hierarchical intervention techniques, namely; instruction, modeling, role playing, feedback, and ownwork/applying skills outside the group setting. The results of the implementation of this training based on a pre-post questionnaire showed an increase in pre-post results from an average of 28 to an average of 41.08. While the results of data processing using SPSS obtained the value of Sig. 0.05 this indicates a significant difference between the pretest and posttest. Thus, SLA can increase the independence of rejected elementary school students